Intraspecific variation in resistance of frog eggs to fungal infection - Sagvik, J; Uller, T; Stenlund, T; Olsson, M (2008)
Documenting sources of variation in host viability at pathogen exposure within and among populations is an important task in order to predict host-pathogen evolutionary dynamics. In the present study, we investigated family and population variation in the degree of embryonic infection of the pathogenic fungus Saprolegnia spp., by infecting moor frog (Rana arvalis) eggs from six populations and exposing them to two different temperatures. We found a significant family effect on the degree of Saprolegnia-infection of eggs and embryos, suggesting that there is genetic variation in resistance among embryos, or variation among females in some aspect of maternally induced resistance. Furthermore, infection level differed significantly between temperatures, with most families having more infected eggs in the relatively colder temperature. However, eggs and embryos from the different populations showed different degrees of Saprolegnia-infection in the two temperatures, i.e., there was a significant population × temperature interaction on the proportion of infected eggs. Thus, the degree of Saprolegnia-infection is sensitive to variation at the level of the family, population and environmental conditions, suggesting that responses to fungal outbreaks will vary geographically and will be difficult to predict. © 2007 Springer Science+Business Media, Inc.